Perovskite composite aerogel catalyst as well as preparation method and application thereof

By evenly dispersing perovskites in porous carbon aerogels, a perovskite composite aerogel catalyst was prepared, which solved the problems of insufficient stability and electron transfer rate of traditional catalysts when treating salt-containing organic wastewater, and achieved more efficient deep wastewater treatment.

CN119657115APending Publication Date: 2025-03-21BEIJING UNIV OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411665241.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

When treating salt-containing organic wastewater, existing metal oxide catalysts have bottleneck problems such as easy agglomeration and loss of metal components and low free radical yields, and traditional catalyst stability and electron transfer rate are insufficient.

Method used

A perovskite composite aerogel catalyst was designed, and prepared by uniformly dispersing the perovskite in the porous carbon aerogel formed after calcination, using the cross-linking reaction of sodium alginate and Ca2+, and through ultrasonic dispersion, freeze-drying and high-temperature calcination.

Benefits of technology

The electron transfer rate and catalytic performance of perovskites are improved, the absorption capacity of ozone and pollutants is enhanced, and more efficient deep treatment of salt-containing organic wastewater is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657115A_ABST
    Figure CN119657115A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite aerogel composite catalyst, which is composed of a porous carbon aerogel and a perovskite active component loaded on the porous carbon aerogel, the molecular structure of perovskite is Ca < 1.1 > MnO < 3-delta >, delta is oxygen vacancy, and the value is 0-1. Perovskite in the catalyst serves as a main active substance and is uniformly dispersed in porous carbon aerogel formed after calcination, the electron transfer rate of the perovskite can be effectively increased due to the existence of a porous carbon structure, and the carbon structure has a high specific surface area and can promote absorption of the catalyst to ozone and pollutants; therefore, the catalyst is easier to contact with active sites on perovskite, and the catalytic performance of the catalyst is improved, so that the catalyst with high activity and good stability is obtained. The catalyst provided by the invention is oriented to deep treatment of salt-containing organic wastewater, has good catalytic performance, is good in stability, can be repeatedly used, does not observe activity reduction, and is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and relates to a perovskite composite aerogel catalyst for deep treatment of saline organic wastewater by ozone catalytic oxidation, and a preparation method and application thereof. Background Art

[0002] Salt-containing organic wastewater has a complex composition and poor biodegradability. It is a difficult-to-treat industrial wastewater with "three-hazard" toxicity. Its deep treatment is of great significance and extremely challenging. Heterogeneous ozone catalytic oxidation technology is one of the effective ways to deeply treat petrochemical wastewater. The core lies in the development of efficient catalysts and the enhanced generation of free radicals. At present, there are key bottlenecks such as the easy loss of metal component agglomeration and low free radical production. In order to degrade salt-containing organic wastewater with complex components, advanced oxidation processes that can produce highly active intermediates stand out. Ozone catalytic oxidation (CWOO) can accelerate the decomposition of ozone and the generation of free radicals, with a high degree of mineralization, and has a good application scenario in the treatment of difficult-to-degrade organic wastewater; and the raw materials are easy to obtain, and only oxygen ionization is required to produce it. The production is simple, suitable for industrial applications, and has a wide range of application scenarios. The addition of catalysts effectively improves the utilization rate of ozone, further reducing the cost of the enterprise. Heterogeneous ozone catalytic oxidation technology is currently a widely used wastewater treatment technology in industry. It has the advantages of easy catalyst recovery, strong activity retention, and low risk of secondary pollution, which makes it widely used in industrial production. It is also the current research focus in the direction of ozone catalytic oxidation.

[0003] Various metal oxides have been reported as catalyst materials for catalytic ozonation, such as manganese dioxide (MnO 2 ), iron oxide (Fe 2 O 3 / Fe 3 O 4 ), cerium oxide (CeOx) and cobalt oxide (Co 3 O 4 ) etc. However, the leaching and loss of metal components in traditional transition metal oxide catalysts limit their application, and the slow electron transfer process further hinders the improvement of catalyst performance. Compared with single metal oxides, catalysts with special structures (ABO 3) may have higher catalytic reaction activity. Due to the bonding between the two metal ions, bimetallic oxides are also more stable as catalysts than traditional metal oxides. In addition, perovskite catalysts have attractive catalytic efficiency and stability due to their tunable structure, which has attracted increasing interest in the field of heterogeneous catalysis. It is worth noting that perovskite catalysts usually have small specific surface area and pore volume, which can easily hinder the exposure of active sites, and are not conducive to electron transfer and the generation of reactive oxygen species. Therefore, how to design and synthesize perovskite catalysts with high specific surface area and developed pore structure, improve the electron transfer rate, and enhance the generation of reactive oxygen species is an urgent problem to be solved and one of the important research directions in the future. Summary of the invention

[0004] One of the purposes of the present invention is to provide a perovskite composite aerogel catalyst for deep treatment of salt-containing organic wastewater by ozone catalytic oxidation in response to the problems existing in the prior art; in the catalyst, perovskite as the main active substance is uniformly dispersed in the porous carbon aerogel formed after calcination, and has high catalytic performance.

[0005] The second object of the present invention is to provide a method for preparing the above-mentioned perovskite composite aerogel catalyst. The method is used to prepare the perovskite composite aerogel catalyst, the process is simple, the main active substances are evenly distributed in the porous carbon aerogel, and the catalyst has high catalytic performance.

[0006] To this end, the first aspect of the present invention provides a perovskite composite aerogel catalyst, which is composed of a porous carbon aerogel and a perovskite active component supported on the porous carbon aerogel, wherein the molecular structure of the perovskite is Ca 1.1 MnO 3-δ , δ is the oxygen vacancy, and its value ranges from 0 to 1.

[0007] In some embodiments of the present invention, the porous carbon aerogel is sodium alginate aerogel, and the perovskite composite aerogel catalyst uses perovskite as the main active site and reacts with sodium alginate and Ca 2+ Made by cross-linking and high temperature calcination.

[0008] Preferably, the sodium alginate aerogel is modified with a modifier, and the modifier includes one or more of chitosan, liquid silicon, phenolic resin, pectin and gelatin.

[0009] In the present invention, the specific surface area of ​​the perovskite composite aerogel catalyst is 200-240m 2 / g, pore volume is 0.05-0.2cm 3 / g.

[0010] The second aspect of the present invention provides a method for preparing the perovskite composite aerogel catalyst according to the first aspect of the present invention, comprising:

[0011] Step A, preparation of perovskite Ca by sol-gel method 1.1 MnO 3-δ ;

[0012] Step B, mixing sodium alginate aqueous solution with perovskite Ca 1.1 MnO 3-δ Mixing and ultrasonic stirring to obtain a sodium alginate-perovskite mixed solution;

[0013] Step C, add the modifier to the sodium alginate-perovskite mixture, stir thoroughly, and then add dropwise to the Ca 2+ In aqueous solution, cross-linking into balls, filtering, washing, and obtaining perovskite composite aerogel balls;

[0014] Step D, freeze-drying the perovskite composite aerogel to obtain a catalyst precursor;

[0015] Step E: calcining the catalyst precursor to obtain a perovskite composite aerogel catalyst.

[0016] According to the method of the present invention, in step B, the concentration of the sodium alginate aqueous solution is 1wt%-5wt%.

[0017] In some embodiments of the present invention, in step C, the mass ratio of the perovskite, the modifier and the sodium alginate is (0.01-0.1):(5-40):1.

[0018] According to the present invention, the Ca 2+ The aqueous solution is composed of Ca(NO 3 ) 2 ·4H 2 O is dissolved in water to form; preferably, the Ca 2+ The concentration of the aqueous solution is 0.1 mol / L; further preferably, the Ca 2+ The volume ratio of the aqueous solution to the sodium alginate aqueous solution is 2:1.

[0019] In some embodiments of the present invention, in step D, the freeze-drying temperature is -60°C to -40°C, and the freeze-drying time is 6-48 hours.

[0020] According to the method of the present invention, in step E, calcination is carried out under an inert gas atmosphere; preferably, the calcination temperature is 600-1000° C.; and / or the calcination time is 1-5 h.

[0021] The third aspect of the present invention provides the use of the perovskite composite aerogel catalyst as described in the first aspect of the present invention or the perovskite composite aerogel catalyst prepared by the preparation method as described in the second aspect of the present invention in the deep treatment of saline organic wastewater.

[0022] In some embodiments of the present invention, the application includes loading an ozone oxidation catalyst into a wastewater treatment device, introducing salt-containing organic wastewater and ozone, performing ozone oxidation treatment on the wastewater, and obtaining oxidized effluent that meets emission standards.

[0023] The beneficial effects of the present invention are as follows:

[0024] The present invention proposes to prepare a perovskite composite aerogel catalyst by combining perovskite with carbon aerogel. In the catalyst, perovskite as the main active substance is uniformly dispersed in the carbon spheres formed after calcination. The presence of the porous carbon structure can effectively increase the electron transfer rate of the perovskite. The high specific surface area of ​​the carbon structure can also promote the catalyst's absorption of ozone and pollutants, making it easier for it to contact with the active sites on the perovskite, thereby improving the catalytic performance of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention is further described below in conjunction with the accompanying drawings.

[0026] Figure 1 Shows Ca 1.1 MnO 3-δ -C catalyst preparation process, wherein (a) is sodium alginate and Ca 2+ Cross-linking process, (b) is the catalyst precursor before freeze-drying, (c) is the catalyst precursor after freeze-drying, and (d) is the catalyst precursor formed into a catalyst after calcination.

[0027] Figure 2 Ca at different magnifications (ad) 1.1 MnO 3-δ -SEM image of the C catalyst. DETAILED DESCRIPTION

[0028] To make the present invention easy to understand, the present invention will be described in detail below in conjunction with examples. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.

[0029] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.

[0030] I. Terminology

[0031] The term "TDS" (Total dissolved solids) used in the present invention is also called the total amount of dissolved solids, and is measured in milligrams per liter (mg / L), which indicates how many milligrams of dissolved solids are dissolved in 1 liter of water. The higher the TDS value, the more dissolved substances are contained in the water. Total dissolved solids refer to the total amount of all solutes in the water, including both inorganic and organic substances. Generally, the conductivity value can be used to roughly understand the salt content in the solution. Generally, the higher the conductivity, the higher the salt content, and the higher the TDS. Therefore, TDS also reflects the salt level in the wastewater.

[0032] The term "deep wastewater treatment" mentioned in the present invention generally refers to the further treatment of residual organic matter in the secondary effluent after biochemical treatment by using advanced oxidation technology.

[0033] The "Ca" in the present invention 1.1 MnO 3-δ ” is the molecular structure of perovskite, where δ is the oxygen vacancy and takes a value of 0-1.

[0034] The term "Ca" in the present invention 1.1 MnO 3-δ The “C” in “-C” refers to carbon aerogel, and the “-” means that the perovskite is supported on the carbon aerogel.

[0035] The term "water" in the present invention refers to deionized water, distilled water or ultrapure water unless otherwise specified.

[0036] II. Implementation Plan

[0037] As mentioned above, there is room for further exploration of existing supported metal oxide catalysts. For example, there are key bottleneck problems such as easy aggregation and loss of metal components and low free radical yield. In particular, the heavy metal ion pollution formed will bring difficulties to subsequent treatment. At the same time, supported metal oxide catalysts require the use of a large amount of carriers, the pretreatment process is complicated, and the cost of use is high. In view of this, the inventors have conducted a lot of research on the deep treatment of saline organic wastewater by ozone oxidation technology.

[0038] The inventors have found that compared with simple metal oxides, perovskite has a special structure. The A / B metals can cooperate with each other during the reaction to improve the catalytic effect of the catalyst; and its special crystal structure makes its stability significantly higher than that of ordinary metal oxides. The above advantages make it an emerging catalyst with high catalytic activity and environmental friendliness. 2+Ionic crosslinking and mixed calcination with perovskite can form a perovskite composite aerogel catalyst with perovskite as the active center. The combination of perovskite and carbon aerogel (physically) increases the specific surface area of ​​the catalyst. The presence of the porous carbon structure can effectively improve the electron transfer rate of the perovskite. The high specific surface area of ​​the carbon structure can also promote the catalyst's absorption of ozone and pollutants, making it easier to contact the active sites on the perovskite, thereby improving the catalytic performance of the catalyst.

[0039] Therefore, the novel perovskite composite aerogel catalyst for deep treatment of saline organic wastewater by ozone catalytic oxidation involved in the first aspect of the present invention is composed of a porous carbon aerogel and a perovskite active component supported on the porous carbon aerogel.

[0040] The perovskite composite aerogel catalyst provided in this paper mainly has Mn sites and has higher catalytic activity. In the catalyst, the molecular structure of perovskite is Ca 1.1 MnO 3-δ Due to the excessive regulation of Ca sites, a small amount of excess will not affect the structure of perovskite, resulting in the formation of oxygen vacancies. Therefore, we use δ to represent oxygen vacancies. The value range of δ obtained according to the specific preparation process is between 0 and 1. Perovskite has high catalytic efficiency and high stability, can be recycled repeatedly, and is the active component of perovskite composite aerogel catalyst.

[0041] According to the present invention, the catalyst uses perovskite as the main active site and utilizes sodium alginate and Ca 2+ The cross-linking is obtained by ultrasonic dispersion-freeze drying-high temperature calcination.

[0042] Based on the above, it is easy to understand that the perovskite composite aerogel catalyst of the present invention is composed of Ca 2+ The cross-linked reaction product of ions and sodium alginate and perovskite are formed by high temperature calcination; preferably, the Ca 2+ Modifiers were also added during the cross-linking process between ions and sodium alginate.

[0043] In the present invention, the modifier includes one or more of chitosan, liquid silicon, phenolic resin, pectin and gelatin.

[0044] The above perovskite composite aerogel catalyst can be expressed as Ca 1.1 MnO 3-δ -C.

[0045] In some embodiments of the present invention, the specific surface area of ​​the perovskite composite aerogel catalyst is 200-240m 2 / g, preferably 210-240m 2 / g; pore volume is 0.05-0.2cm 3 / g, preferably 0.055-0.2cm3 / g.

[0046] like Figure 1 As shown, the preparation method of the perovskite composite aerogel catalyst as described in the first aspect of the present invention involved in the second aspect of the present invention comprises:

[0047] Step A, preparing the perovskite catalyst Ca by citrate sol-gel method 1.1 MnO 3-δ ;

[0048] Step B, prepare a sodium alginate aqueous solution, add the prepared perovskite catalyst Ca 1.1 MnO 3-δ , mixing by ultrasonic stirring to obtain a sodium alginate-perovskite mixed solution;

[0049] Step C, add a modifier to the sodium alginate-perovskite mixture, stir it thoroughly, place it in a separatory funnel, and add it dropwise to the mixture containing Ca 2+ The solution is cross-linked into balls, filtered, and washed to obtain perovskite composite aerogel balls (a);

[0050] Step D, freeze-drying the perovskite composite aerogel beads (b) to obtain a catalyst precursor (c);

[0051] Step E: calcining the catalyst precursor to obtain a perovskite composite aerogel catalyst (d).

[0052] According to the method of the present invention, in step B, the concentration of the sodium alginate aqueous solution is 1wt%-5wt%.

[0053] Since the perovskite composite aerogel catalyst of the present invention uses perovskite as the main active site, the sodium alginate and Ca 2+ The cross-linking is obtained by ultrasonic dispersion-freeze drying-high temperature calcination. Therefore, it is important to examine the amount of perovskite.

[0054] For example, in some specific embodiments of the present invention, in step B, different amounts of perovskite are added to a sodium alginate solution with a concentration of 1wt%-5wt%, so as to examine the optimal amount of perovskite added in subsequent steps. The research results show that when the perovskite addition amount is 0.6g / L (2wt% sodium alginate), the activity and stability of the obtained calcium-based porous carbon sphere catalyst are higher.

[0055] As a further improvement of the present invention, it is proposed to use a modifier in the catalyst preparation process, which is beneficial to improve the mechanical strength of the gel beads formed by cross-linking and improve the stability of the catalyst.

[0056] Preferably, the modifier is one or more of chitosan, liquid silicon, phenolic resin, pectin and gelatin.

[0057] Specifically, the cross-linking process of the present invention is based on the sodium alginate solution and Ca 2+ The reaction between ions, the modifier mainly improves the stability of the catalyst.

[0058] In some preferred embodiments of the present invention, the prepared mixed solution of perovskite-sodium alginate and modifier (sodium alginate-perovskite-modifier mixed solution) is gradually added dropwise to the mixture containing Ca 2+ The mixture is added into an aqueous solution and magnetically stirred at 20-35° C. for 1-5 hours, filtered and washed with water; preferably, the mass ratio of the perovskite, the modifier and the sodium alginate is (0.01-0.1):(5-40):1.

[0059] In some embodiments of the present invention, in step D, the freeze-drying temperature is -60°C to -40°C, and the freeze-drying time is 6-48 hours.

[0060] In some other embodiments of the present invention, in step E, calcination is carried out under an inert gas atmosphere at a temperature of 600-1000° C. and a calcination time of 1-5 h.

[0061] In the present invention, the Ca 2+ The aqueous solution is composed of calcium nitrate (Ca(NO 3 ) 2 ·4H 2 O) is dissolved in water, preferably, the Ca 2+ The concentration of the aqueous solution is 0.1 mol / L; further preferably, the Ca 2+ The volume ratio of the aqueous solution to the sodium alginate aqueous solution is 2:1.

[0062] In some specific preferred embodiments of the present invention, the Ca2+ gel is prepared by a citrate sol-gel method. 1.1 MnO 3-δ The methods include:

[0063] Step A, a stoichiometric Ca(NO 3 ) 2 ·4H 2 O and Mn(NO 3 ) 2 Dissolved in a mixture of ultrapure water and ethanol (the volume ratio of ethanol to water is 3:2) to obtain a metal ion mixture;

[0064] Step B, slowly adding citric acid (the molar ratio of total metal ions to citric acid is 1:1) to the above metal ion mixture, stirring at room temperature for 3 hours to mix evenly, to obtain a catalyst precursor mixture;

[0065] Step C, heat-treating the obtained mixture in an oil bath at 80° C. for 6 h to form a light yellow gel, and drying it in an oven at 110° C. for 12 h to obtain a catalyst precursor;

[0066] Step D, calcining the catalyst precursor at 800° C. for 4 h to obtain an oxygen vacancy-rich perovskite catalyst.

[0067] In the above preparation method, Mn(NO 3 ) 2 The purchased concentration solution was added, Mn(NO 3 ) 2 The concentration of the solution is 50wt%; the Mn(NO 3 ) 2 The dosage (working concentration) is 0.004 mol / L, Ca(NO 3 ) 2 ·4H 2 The amount of O is Mn(NO 3 ) 2 1.1 times the dosage.

[0068] The third aspect of the present invention provides an application of the perovskite composite aerogel catalyst as described in the first aspect of the present invention or the perovskite composite aerogel catalyst prepared by the preparation method as described in the second aspect of the present invention in the deep treatment of saline organic wastewater; it can be understood as a method for deep treatment of saline organic wastewater using the perovskite composite aerogel catalyst as described in the first aspect of the present invention or the perovskite composite aerogel catalyst prepared by the preparation method as described in the second aspect of the present invention.

[0069] Specifically, the application includes loading an ozone oxidation catalyst in a wastewater treatment device, introducing saline organic wastewater and ozone, performing ozone oxidation treatment on the wastewater, and obtaining oxidized effluent that meets emission standards.

[0070] The salt-containing organic wastewater in the present invention includes but is not limited to biochemical effluent from chemical industrial parks and / or petrochemical wastewater.

[0071] In some embodiments of the present invention, the reaction conditions of ozone oxidation treatment are: COD of the wastewater: 140-160 mg / L, TDS: 2700-2710 mg / L, pH = 7.5, ozone flow rate is 0.03 L / min, catalyst loading amount is 200 g / L, reaction time is 60 min, and ozone addition ratio is 0.6-4.2.

[0072] Experimental results show that the COD removal rate of petrochemical wastewater treated with the ozone oxidation catalyst of the present invention is ≥42%, and even as high as 62.00%.

[0073] The present invention mainly proposes to prepare a perovskite composite aerogel catalyst by combining perovskite with carbon aerogel (physical). In the catalyst, perovskite as the main active substance is evenly dispersed in the carbon sphere (porous carbon aerogel) formed after calcination. The presence of the porous carbon structure can effectively increase the electron transfer rate of the perovskite. The high specific surface area of ​​the carbon structure can also promote the catalyst to absorb ozone and pollutants, making it easier to contact with the active sites on the perovskite, thereby improving the catalytic performance of the catalyst. The catalyst uses perovskite as the main active site and utilizes sodium alginate and Ca 2+ The cross-linking process was carried out, the catalyst stability was improved by adding a modifier, and a new and efficient perovskite composite aerogel catalyst was designed and synthesized by ultrasonic dispersion-freeze drying-high temperature calcination. The catalyst is suitable for the deep treatment of saline organic wastewater, has good catalytic performance, and has good catalyst stability and can be reused. No decrease in activity was observed, and it is suitable for industrial promotion.

[0074] III. Examples

[0075] The present invention is further described in detail below through the accompanying drawings and specific examples. The experimental methods described below, unless otherwise specified, are all routine laboratory methods. The experimental materials described below, unless otherwise specified, can all be obtained from commercial channels.

[0076] In the following examples, COD was determined by digestion using Hach COD reagent on a Hach DRB200 digestion instrument (Hach Company, USA), and then measured using a DR5000 UV spectrophotometer (Hach Company, USA). TDS was determined using a DDSJ-319L conductivity meter (Shanghai Leici Instrument Co., Ltd.). COD removal rate was calculated according to the following formula:

[0077] COD removal rate = (COD 原始 -COD 氧化后 ) / COD 原始 ×100%

[0078] Embodiment 1:

[0079] (1) Weighing different perovskites, 0.02 g, 0.04 g, 0.06 g, 0.08 g, and 1 g, respectively, and adding 100 mL of a 2.0 wt% sodium alginate solution prepared, with phenolic resin as a modifier, and the mass ratio of phenolic resin to sodium alginate is 20:1;

[0080] (2) After the mixed solution of perovskite and sodium alginate was fully ultrasonically stirred for 4 h, phenolic resin was added to the above solution, stirred for 1 h, placed in a separatory funnel, and gradually added dropwise to 0.1 mol / L Ca(NO 3 ) 2 The solution was cross-linked into balls, filtered and washed with water, and placed in a freeze dryer at -50°C for 24 hours to obtain a catalyst precursor;

[0081] (3) The catalyst precursor was placed in an inert gas atmosphere in a tubular furnace and calcined at 800° C. for 2 h to obtain a perovskite composite aerogel catalyst.

[0082] Reaction conditions: petrochemical wastewater reverse osmosis concentrated water, COD: 140-160mg / L, TDS: 2700-2710mg / L, wastewater volume: 1000ml, pH=7.5, ozone flow rate of 0.03L / min, catalyst loading of 36g / L, reaction time of 60min, ozone concentration of 12mg / L.

[0083] The experimental results show that Ca 1.1 MnO 3-δ -C catalyst COD removal rate is between 42-52%.

[0084] Embodiment 2:

[0085] (1) preparing 100 mL of 2.0 wt% sodium alginate solution, adding 0.06 g of titanium ore, using phenolic resin as a modifier, and the mass ratio of phenolic resin to sodium alginate is 20:1;

[0086] (2) After the mixed solution of perovskite and sodium alginate was fully ultrasonically stirred for 4 h, phenolic resin was added to the above solution, stirred for 1 h, placed in a separatory funnel, and gradually added dropwise to 0.1 mol / L Ca(NO 3 ) 2 The solution was cross-linked into balls, filtered and washed with water, and placed in a freeze dryer at -50°C for 24 hours to obtain a catalyst precursor;

[0087] (3) The catalyst precursor is placed in an inert gas atmosphere in a tubular furnace and calcined at 600-1000° C. for 2 h to obtain a perovskite composite aerogel catalyst.

[0088] Reaction conditions: petrochemical wastewater reverse osmosis concentrated water, COD: 140-160mg / L, TDS: 2700-2710mg / L, wastewater volume: 1000ml, pH=7.5, ozone flow rate of 0.03L / min, catalyst loading of 60g / L, reaction time of 60min, and ozone concentration of 12mg / L.

[0089] The experimental results show that Ca1.1 MnO 3-δ -C catalyst COD removal rate is between 32-62%.

[0090] Embodiment 3:

[0091] (1) Prepare 100 mL of 2.0 wt% sodium alginate solution, add 0.06 g of titanium ore, use phenolic resin as a modifier, and the mass ratio of phenolic resin to sodium alginate is 20:1;

[0092] (2) After the mixed solution of perovskite and sodium alginate was fully ultrasonically stirred for 4 h, phenolic resin was added to the above solution, stirred for 1 h, placed in a separatory funnel, and gradually added dropwise to 0.1 mol / L Ca(NO 3 ) 2 The solution was cross-linked into balls, filtered and washed with water, and placed in a freeze dryer at -50°C for 24 hours to obtain a catalyst precursor;

[0093] (3) The catalyst precursor was placed in an inert gas atmosphere in a tubular furnace and calcined at 800° C. for 2 h to obtain a perovskite composite aerogel catalyst.

[0094] Reaction conditions: petrochemical wastewater reverse osmosis concentrated water, COD: 140-160mg / L, TDS: 2700-2710mg / L, wastewater volume: 1000ml, pH=7.5, ozone flow rate of 0.03L / min, catalyst loading of 60g / L, reaction time of 60min, ozone concentration of 4-20mg / L.

[0095] The experimental results show that Ca 1.1 MnO 3-δ -C catalyst COD removal rate is between 45-55%.

[0096] Embodiment 4:

[0097] (1) Prepare 100 mL of 2.0 wt% sodium alginate solution, add 0.06 g of titanium ore, use phenolic resin as a modifier, and the mass ratio of phenolic resin to sodium alginate is 20:1;

[0098] (2) After the mixed solution of perovskite and sodium alginate was fully ultrasonically stirred for 4 h, phenolic resin was added to the above solution, stirred for 1 h, placed in a separatory funnel, and gradually added dropwise to 0.1 mol / L Ca(NO 3 ) 2 The solution was cross-linked into balls, filtered and washed with water, and placed in a freeze dryer at -50°C for 24 hours to obtain a catalyst precursor;

[0099] (3) The catalyst precursor is placed in an inert gas atmosphere in a tubular furnace and calcined at 600-1000° C. for 2 h to obtain a perovskite composite aerogel catalyst.

[0100] Reaction conditions: petrochemical wastewater reverse osmosis concentrated water, COD: 140-160mg / L, TDS: 2700-2710mg / L, wastewater volume: 1000ml, pH=7.5, ozone flow rate of 0.03L / min, catalyst loading of 60g / L, reaction time of 60min, and ozone concentration of 12mg / L.

[0101] The experimental results show that Ca 1.1 MnO 3-δ -C catalyst COD removal rate is between 32-62%.

[0102] Embodiment 5:

[0103] (1) Prepare 100 mL of 2.0 wt% sodium alginate solution, add 0.06 g of titanium ore, use phenolic resin as a modifier, and the mass ratio of phenolic resin to sodium alginate is 20:1;

[0104] (2) After the mixed solution of perovskite and sodium alginate was fully ultrasonically stirred for 4 h, phenolic resin was added to the above solution, stirred for 1 h, placed in a separatory funnel, and gradually added dropwise to 0.1 mol / L Ca(NO 3 ) 2 The solution was cross-linked into balls, filtered and washed with water, and placed in a freeze dryer at -50°C for 24 hours to obtain a catalyst precursor;

[0105] (3) The catalyst precursor was placed in an inert gas atmosphere in a tubular furnace and calcined at 800° C. for 2 h to obtain a perovskite composite aerogel catalyst.

[0106] The Ca in this example was observed under different magnifications by scanning electron microscopy (GeminiSEM-300, ZEISS). 1.1 MnO 3 -C catalyst microstructure, the results are as follows Figure 2 shown.

[0107] Through electron microscopy ( Figure 2 ) The porous structure of the perovskite composite aerogel catalyst can be observed, and the rich pore structure can provide a place for the ozone catalytic oxidation reaction, which is beneficial to improving the process efficiency.

[0108] Reaction conditions: petrochemical wastewater reverse osmosis concentrated water, COD: 140-160mg / L, TDS: 2700-2710mg / L, wastewater volume: 1000ml, pH=7.5, ozone flow rate of 0.03L / min, catalyst loading of 60g / L, reaction time of 60min, and ozone concentration of 12mg / L.

[0109] The experimental results show that Ca 1.1 MnO 3-δ -C catalyst COD removal efficiency is 55%.

[0110] It should be noted that the embodiments described above are only preferred embodiments of the present invention, which are used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A perovskite composite aerogel catalyst, which is composed of a porous carbon aerogel and a perovskite active component supported on the porous carbon aerogel, wherein: The molecular structure of the perovskite is Ca 1.1 MnO 3-δ , δ is the oxygen vacancy, and its value ranges from 0 to 1.

2. The perovskite composite aerogel catalyst according to claim 1, characterized in that: The porous carbon aerogel is a sodium alginate aerogel, and the perovskite composite aerogel catalyst uses perovskite as the main active site and reacts with sodium alginate and Ca 2+ Made by cross-linking and high temperature calcination.

3. The perovskite composite aerogel catalyst according to claim 2, characterized in that: The sodium alginate aerogel is modified by a modifier, and the modifier includes one or more of chitosan, liquid silicon, phenolic resin, pectin and gelatin.

4. The perovskite composite aerogel catalyst according to any one of claims 1 to 3, characterized in that: The specific surface area of ​​the perovskite composite aerogel catalyst is 200-240m 2 / g, pore volume is 0.05-0.2cm 3 / g.

5. The method for preparing the perovskite composite aerogel catalyst according to any one of claims 1 to 4, comprising: Step A, preparation of perovskite Ca by sol-gel method 1.1 MnO 3-δ ; Step B, mixing sodium alginate aqueous solution with perovskite Ca 1.1 MnO 3-δ Mixing and ultrasonic stirring to obtain a sodium alginate-perovskite mixed solution; Step C, add the modifier to the sodium alginate-perovskite mixture, stir thoroughly, and then add dropwise to the Ca 2+ In aqueous solution, cross-linking into balls, filtering, washing, and obtaining perovskite composite aerogel balls; Step D, freeze-drying the perovskite composite aerogel to obtain a catalyst precursor; Step E: calcining the catalyst precursor to obtain a perovskite composite aerogel catalyst.

6. The preparation method according to claim 5, characterized in that: In step B, the concentration of the sodium alginate aqueous solution is 1wt%-5wt%.

7. The preparation method according to claim 5, characterized in that: In step C, the mass ratio of the perovskite, the modifier and the sodium alginate is (0.01-0.1):(5-40):1; and / or, the Ca 2+ The aqueous solution is formed by dissolving Ca(NO3)2·4H2O in water; preferably, the Ca 2+ The concentration of the aqueous solution is 0.1 mol / L; further preferably, the Ca 2+ The volume ratio of the aqueous solution to the sodium alginate aqueous solution is 2:

1.

8. The preparation method according to claim 5, characterized in that: In step D, the freeze-drying temperature is -60°C to -40°C, and the freeze-drying time is 6-48 hours.

9. The preparation method according to claim 5, characterized in that: In step E, calcination is performed under an inert gas atmosphere; preferably, the calcination temperature is 600-1000° C.; and / or the calcination time is 1-5 h.

10. Use of the perovskite composite aerogel catalyst according to any one of claims 1 to 4 or the perovskite composite aerogel catalyst prepared by the preparation method according to any one of claims 5 to 9 in the deep treatment of saline organic wastewater; preferably, the use comprises loading the perovskite composite aerogel catalyst into a wastewater treatment device, passing saline organic wastewater and ozone, performing ozone oxidation treatment on the wastewater, and obtaining oxidized effluent that meets emission standards.

Citation Information

Patent Citations

  • Preparation method and use of three-dimensional nano-perovskite-type composite heterogeneous Fenton catalyst

    CN103785394A

  • Copper-loaded sodium alginate carbon aerogel and preparation method and application thereof

    CN109650373A

  • MXene / sodium alginate derived carbon three-dimensional aerogel as well as preparation method and application thereof

    CN111422873A

  • Preparation of CdIn2S4 composite carbon aerogel photocatalyst and application of CdIn2S4 composite carbon aerogel photocatalyst in synthesis of xylonic acid by photocatalytic oxidation of xylose

    CN114870868A

  • Calcium-based porous carbon sphere catalyst for deep treatment of salt-containing organic wastewater by catalytic ozonation

    CN115025767A